Access to Psychotherapy in the Era of Web 2.0 - New Media, Old Inequalities? / Zugang zur Psychotherapie in der Ära des Web 2.0 - Neue Medien, Alte Ungleichheiten? - Apolinario-Hagen Jennifer Anette; Tasseit Siegfried (Sciendo, 2015)
Background: Currently, the debate on regional and socio-structurally related treatment gaps in psychotherapeutic care increases the interest in e-mental health interventions such as the Internet-based psychotherapy, online self-help and new approaches for self-empowerment. Thus, health professionals could support informed decision-making by knowing the latest developments. However, if the 'digital revolution' fails to reach patients not familiar with Web 2.0, access to psychotherapies is unlikely to improve. Therefore, the objective of this review is to clarify whether online therapies should be recommended as an effective alternative to conventional psychotherapy in primary care.